PERSUASIVE STRATEGIES USED BY INSURANCE AGENTS IN PROSPECTING CUSTOMERS BASED ON THE CUSTOMERS’ AGE FACTOR - Olivia Olga Wijaya; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
This study aimed to find out the persuasive strategies used by X insurance agents in prospecting the customers and reveal the differences and similarities between persuasive strategies used by insurance agents in prospecting same-age customers and older customers. Through this study, the writer tried to relate the persuasive strategies used by insurance agents to the customers’ age factor. The writer chose three insurance agents who worked in X Insurance company and classified the customers into two categories based on their ages; firstly, customers who are in the same-age group as the agents; secondly, customers who are in different-age (older) group from the agents. In the findings, it turned out that in prospecting both customers’ categories, the insurance agents used both persuasive strategies proposed by Beebe & Beebe (2012); however some methods of persuasion strategies were not used at all. This study concluded that the age of the customers does not really affect the way insurance agents prospect their customers.